O’ZBEK ALLALARIGA PSIXOLINGVISTIK YONDASHUV - Karimova, F.S. (SCIENCE and SOCIETY, 2022)
The article shows the psycholinguistic approach to Uzbek lullaby texts, showing that the words that make up the text are related to the mental state of the mother.